Radiofrequency Heating and High-Intensity Focused Electromagnetic Treatment Delivered Simultaneously: The First Sham-Controlled Randomized Trial. Issue 5 (9th March 2022) - Samuels, Julene B.; Katz, Bruce; Weiss, Robert A.
Abstract : Background: Radiofrequency-based and high-intensity focused electromagnetic (HIFEM)-based devices have proved effective and safe for abdominal body shaping. Radiofrequency is known to reduce adipose tissue, whereas HIFEM treatment is effective for muscle definition. The authors investigated the efficacy of a novel device delivering synchronized radiofrequency and HIFEM treatment simultaneously for abdominal toning and fat reduction. Methods: Seventy-two patients were enrolled and randomly divided into active ( n = 48; age, 45.5 ± 13.0 years) and sham groups ( n = 24; age, 44.6 ± 12.3 years). Both groups received three treatments on the abdomen once a week. The intensity in the active group was set to maximum tolerable level; in the sham group, the intensities were set to 5 percent. Ultrasound images were taken before treatment and at 1, 3, and 6 months after treatment to examine changes in subcutaneous fat and rectus abdominis muscle thickness. Digital photographs were taken, and satisfaction and therapy comfort were assessed. Results: Ultrasound images of the active group at 1 month showed significant ( p < 0.05) reduction in adipose tissue thickness by 20.5 percent (4.8 ± 2.6 mm), whereas rectus abdominis muscle thickness increased by 21.5 percent (2.0 ± 0.8 mm). Results at 3 months improved to 28.3 percent (7.6 ± 3.7 mm) and 24.2 percent (2.3 ± 0.9 mm), respectively. Improvements were maintained at 6 months after treatment in the active group, whereas the sham group showed no significant changes. Treatments were found to be comfortable. The active group showed higher satisfaction with outcomes. Conclusion: Active treatment utilizing simultaneous application of radiofrequency and HIFEM therapy resulted in a significant increase in rectus abdominis thickness and subcutaneous fat reduction, exceeding previously published results for separate HIFEM and radiofrequency treatments. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, II.